PENGEMBANGAN LKS FISIKA BERBASIS PROBLEM SOLVING PADA KELAS X SEMESTER II DI SMA - Pratiwy, Winda Utariny; Lizelwati, Novia; Putra, Amali (Jurnal Pembelajaran MIPA, 2014)
LKSS developmental research physics gets problem solvings basis on brazes x semester II. at SMA aims to result LKS physics gets basis Problem Solving  one that valid, practical and effective for student to braze x semester II. at SMAN 1 Lareh Sago Halaban. This research included research development. This research comprise of three phases which is: define, design, and develop. Feasibility quiz is done on SMAN 1 Lareh Sago Halaban that involves 2 teachers, 3 lecturers and 35 students. In this research have resulted LKS physics gets basis problem solving one that valid, practical and effective. From analisis data can be concluded that (1) Result validate to LKS physics gets basis  problem solving one that is developed for class x semester II. is so valid. (2) test-driving Result those are done at class x 7 at SMAN 1 Lareh Sago Halaban Kab.50 kota point out that have accomplished praktikalitass criterion which is gets to be used and is performed deep learning process. (3) test-driving Result those are done at class x 7 at SMAN 1 Lareh Sago Halaban Kab. 50 kota out that have accomplished effectiveness criterion which is: (a ) Activity studies student increase use LKSs afters physics gets basis problem solving . (b ) Motivation study student increase use LKSs afterses physics gets basis problem solving.  (c ) student Response to learnings with use LKS physics gets basis problem solving really practical. (d. ) Result studies student increase mengunakan LKSs afters physics gets basis problem solving  , with average value brazes 82,73.Key words:  development, LKS, Problem Solving